2001
DOI: 10.1203/00006450-200108000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Loop Diuretics and In Vitro Relaxation of Human Fetal and Newborn Mouse Airways

Abstract: This study was designed to test the hypotheses that furosemide directly causes relaxation in human fetal airway and that delivery of loop diuretics to either the adventitial or epithelial surface of newborn mouse airway results in equivalent relaxation. Isometric tension changes were measured in human fetal (11-16 wk) trachea and mainstem bronchus rings exposed to furosemide (300 M) or saline after acetylcholine or leukotriene D 4 constriction. Significant decreases in isometric tension to furosemide were demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…The response was similar whether the diuretics were applied to the luminal (epithelial) surface or abluminal (adventitial) surface. These results provide additional evidence that there is a direct, non‐epithelial‐dependent effect of furosemide on airway smooth muscle tone and are consistent with the possibility that the Na + –K + –2Cl − cotransporter is present in the human airway smooth muscle cell and that it plays a role in regulating airway tone (61).…”
Section: Effect Of Loop Diuretics On Airwayssupporting
confidence: 82%
See 1 more Smart Citation
“…The response was similar whether the diuretics were applied to the luminal (epithelial) surface or abluminal (adventitial) surface. These results provide additional evidence that there is a direct, non‐epithelial‐dependent effect of furosemide on airway smooth muscle tone and are consistent with the possibility that the Na + –K + –2Cl − cotransporter is present in the human airway smooth muscle cell and that it plays a role in regulating airway tone (61).…”
Section: Effect Of Loop Diuretics On Airwayssupporting
confidence: 82%
“…Iwamoto et al. (61) studied isolated human foetal airway and newborn mouse airways to test the hypothesis that furosemide and bumetanide, both loop diuretics, would cause direct relaxation of human foetal airway. They found that human airway relaxed following furosemide after preconstriction with either acetylcholine or the inflammatory mediator leukotriene D‐4.…”
Section: Effect Of Loop Diuretics On Airwaysmentioning
confidence: 99%
“…The absorptive isoform of the NKCC cotransporter is found exclusively in the renal epithelium (NKCC2), whereas the secretory form (NKCC1) is nearly ubiquitous (8). Although we (9,10) have shown that the NKCC1 cotransporter may be involved in the modification of smooth muscle tone, the primary function of this protein appears to be cell volume regulation, (5,6,13). Cell volume shrinkage initiated by hyperosmolarity will increase cotransporter function, whereas cellular swelling is associated with decreased function.…”
mentioning
confidence: 94%
“…Over the past two decades, clinical and in vitro studies have confirmed airway smooth muscle relaxation responses to these sulfonamide compounds (2,9,11,18,24), but the exact mechanisms mediating their clinical benefits remain controversial. In addition, the widespread presence of this cotransporter protein in various tissues suggests that chronic, systemic administration of NKCC inhibitors may result in other effects that may or may not be beneficial.…”
mentioning
confidence: 99%
“…Thus, in asthmatic patients, treatment of hypertension with ␤-blockers is complicated by their actions as bronchoconstrictors. This is not the case with NKCC1 inhibitors that lead to airway smooth muscle relaxation (9).…”
mentioning
confidence: 98%